Are our Medical Educators Stressed? - Amna Idrees, Minahil Iman Janjua (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Educators face the dual challenge of constant multitasking and time management to maintain their clinical practice along with curriculum development, student assessment, research obligations, and administrative duties. Workload imbalance is one of the foremost causes of stress among medical educators. Although their primary role is teaching, it is undervalued in comparison to research and clinical contributions. This leads to burnout and stress and may lead to health compromise. Objectives: The objectives of this study were to determine the stress levels in teachers of RMU while teaching MBBS students, to assess the correlation of these stress levels with demographic and professional variables such as age, teaching experience, gender, and specialty, and to identify the major stress-causing factors faced by RMU teachers in their academic roles. Materials and methods: A cross-sectional study was conducted in Rawalpindi Medical University from April 2023 to December 2023 through random sampling on 168 teachers of basic sciences, using the DASS-21 questionnaire. Teachers on a month or longer leave during the past three months from data collection were excluded. Data was analyzed on SPSS version 2023. Descriptive analysis was performed, and the Kruskal-Wallis test was used to check the normality of the data. Student t-test and ANOVA were used for significance. Results: The mean distress in the population was scored to be 34.73 ± 24.589, which was highest in the Pharmacology and Pathology Departments, in the age group 31-40 years, and among associate Professors. Excessive workload was reported to be the chief stress-causing factor for most of the participants (n=57, 68.7%), which is a major problem of the repeated examinations in the Integrated Modular Curriculum. Discussion: The study reported normal to moderate distress levels in most of the population. However, a major challenge reported was the excessive amount of workload, with a lack of necessary training for the newly implemented integrated modular systems, which may cause detriment to the personal well-being of the teacher. A good work-life balance and realistic expectations in the workplace may significantly help in reducing stress levels and can prove beneficial to the overall growth of participation satisfaction. Conclusion: Normal to moderate distress levels recorded among most of the medical professionals indicated that while the ever-advancing era of education may be challenging, our educators are well-versed in dealing with such problems. A major challenge proposed may be the increased workload, which can be easily curbed by increasing the number of the taskforce involved. Mesh keywords: Stress, health educator